Intradural-intramedullary intervertebral disc extrusion in a six-month-old Schnauzer - Salinas C., Eben (2023)
Intradural-intramedullary intervertebral disc extrusion (IIVDE) is a subtype of herniation of the hydrated nucleus pulposus and occurs after extreme exercise or traumatic events. IIVDE is a rare condition, and its diagnosis can be complex since its clinical characteristics and images are poorly characterized. The case of a six-month-old Schnauzer who suffered a fall from a height of two stories is reported. The patient developed spastic tetraplegia and was diagnosed as a fourth-degree acute cervical spinal cord injury. The radiographic and computed tomography studies only reported a simple fracture in the vertebral body of C3. The magnetic resonance study reported intramedullary linear tracts, parenchymal lesions and reduced disc volume in C3-C4. The clinical condition and its evolution, as well as the imaging findings were compatible with IIVDE.